Resiquimod induces a mixed Th1 and Th2 response via STAT1 and STAT3 signalling in chickens - Deepthi Kappala; Saravanan Ramakrishnan; Patel Nikunjkumar Prakashbhai; Abinaya Kaliappan; Prasad Thomas; Jörg Linde; Mithilesh Singh; Sohini Dey; Madhan Mohan Chellappa (Biochemistry and Biophysics Reports)
Resiquimod (R-848), a synthetic TLR7 agonist, modulates immune responses, primarily inducing Th1-biased immunity in mammals. In contrast, our previous studies revealed that R-848 stimulates both Th1 and Th2 responses in chickens. The current research investigates the molecular mechanisms underlying these immune responses in chickens. Pooled splenocytes harvested from chickens (n = 2/group) at 24 h post R-848 treatment were subjected to RNA sequencing and significant differentially expressed genes (DEGs) were identified compared to controls. Eight key genes associated with signal transduction (MAPK14, MAP3K8, PIK3CD, STAT1, STAT3, MAPK11, LRRK2, and GATA3) were validated via real-time PCR in chicken peripheral blood mononuclear cells (PBMCs) from six biological replicates. Pharmacological inhibitors or chloroquine were employed to elucidate the signalling pathways. SB202190, IC-87114, and fludarabine phosphate suppressed the R-848-induced expression of MAPK14, PIK3CD, and STAT1, respectively, while chloroquine decreased STAT3 expression. Intriguingly, chloroquine treatment enhanced the R-848-mediated expression of MAPK11, LRRK2, and GATA3. These results align with transcriptomic findings and highlight the upregulation of STAT1 and STAT3 as potential contributors to the induction of Th1 and Th2 immune responses by R-848 in chickens. These insights provide a foundation for optimizing R-848 as an immunomodulatory agent in avian species.